COUPLING OF MEMBRANE BIOREACTOR AND OZONATION FOR REMOVAL OF ANTIBIOTICS FROM HOSPITAL WASTEWATER - Bui Xuan Thanh; Quyen Vo Thi Kim; Phuc Luu Vinh; Tin Nguyen Thanh; Hien Vo Thi Dieu; Thanh Cao Ngoc Dan; Quoc Tuc Dinh (Diponegoro University, 2016)
Antibiotic residues in the environment and their potential toxic effects have been considered as one of the emerging research area in the environmental field. Their continuous introduction in our environment may increase their negative impacts on human health. In this study, the eliminations of antibiotic such as Norfloxacin (NOR), Ciprofloxacin (CIP), Ofloxacin (OFL) and Sulfamethoxazole (SMZ) in wastewater of hospital were processed by membrane bioreactor (MBR) coupled with ozonation process. In particular, the MBR was applied for the antibiotic removals followed by ozonation process as a post-treatment stage to create an adequate integration to enhance removal efficiency. Achieved results after MBR treatment showed that the removal efficiency of NOR, CIP, OFL and SMZ were 90 ± 4.0% , 83 ± 13% , 81 ± 13 % and 39 ± 6%, respectivley. In addition, those antibiotic matters were continously removed by ozonation process with the removal efficiency of 87±9.0% , 83±1.0% , 81±2.3% and 66±2.3% for NOR, CIP, OFL and SMZ, respectively. In summary, antibiotics could be basically limited by the combination of MBR and ozonation before discharging in aquatic environment.